Callitriche von Linne 1753 - Lansdown, Richard V. (Zenodo, 2022)
Key to the taxa occurring in the region Many of the species treated here are allopatric and identification could therefore theoretically be based in part on location. However, the number of non-native species known from or suspected to occur in this and other regions, combined with their distribution, show that the possibility of discovering a taxon new to a particular geographical area is high. This key is therefore designed to enable identification of any of the species suspected to occur in the region independent of locality. An indication of the known distribution of restricted-range species is given to aid decisionmaking. C. muelleri is the only species which can be reliably identified without flowers or fruit; it is the only species in the genus with toothed leaves. 1. Leaves with a single tooth on each margin. 13. C. muelleri - Leaves entire.2 2. Pollen colourless; style reflexed. 4. C. brutia - Pollen yellow; style erect or spreading.3 3. Fruit unwinged or only partially winged.4 - Fruit winged throughout .10 4. Fruit winged at apex, occasionally with narrow wing tapering down the upper parts of the sides ( C. heterophylla fruit may occasionally have a narrow wing at the apex of the fruit. In fresh material, it can be distinguished from C. palustris by the isodiametric fruit, those of C. palustris are longer than wide, however some herbarium material cannot reliably be determined) . .14. C. palustris - Fruit unwinged.5 5. Vegetative parts fleshy and almost succulent; lower leaves reduced to scarious scales . 1. C. antarctica - Vegetative parts not fleshy; leaves either ± homophyllous or lower leaves lingulate, well-formed and green .6 6. Fruit blackish when mature .7 - Fruit pale or golden-brown when mature .9 7. Fruit> 1 mm high and wide (known only from New Guinea). 10. C. fuliginea - Fruit ≤ 1 mm high and wide .8 8. Fruit strumose, wider than high; most axils with both ♀ and ♂ flowers .16. C. peploides - Fruit convex, not strumose, isodiametric; flowers usually solitary (reported in the region only ...